ENVIRONMENT, GROWTH AND BIOMASS PRODUCTION OF SAGO PALM (Metroxylon sagu ROTTB.): A CASE STUDY FROM HALMAHERA, PAPUA AND KENDARI - Yulius B. Pasolon (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2015)
We observed that physical and chemical properties of sago palm growing in three subdistricts of Southeast Sulawesi Province were different with sago growing area in Papua and North Maluku Provinces. Soil texture was loamy to silty loam, BD was 0.598 to 1.360 g/cm3 and water table was 20 to 150 cm depth. Soil pH was 5.21 to 6.34, available P, total N, and exchangeable K, Ca and Mg was low to very low. C-organic was variable from low to very high. Average of monthly rainfall was 56 to 79 mm month-1 in dry season to 200 to 450 mm month-1 in wet season, temperature was 15 to 34o C in Southeast Sulawesi Province. Agronomic characteristics indecated that there are three sago types was observed in Southeast Sulawesi Province, more the seven types of sago palm was observed in Sentani Papua Province and five types of sago palm was observed in Noth Maluku Province. The average of trunk fresh weight was 822 kg/palm on spiny type sago to 2093 kg/palm on nonspiny type sago. Plant age of sago palm at harvest time was 6.40 years after trunk form on spiny type sago and 9.75 year after trunk form on nonspiny type sago. We concluded that the diversity and biomass potential of sago palm grown in Sentani Papua Province was higher than sago palm grown in Maba North Maluku and Southeast Sulawesi Provinces. Key-Words : Agronomic characteristics, Chlorophyll content, Sago palm, Soil properties, Genetic diversity